Ceramic Materials - Wunderlich, Wilfried (IntechOpen, 2010)
This is the first book of a series of forthcoming publications on this field by this publisher. The reader can enjoy both a classical printed version on demand for a small charge, as well as the online version free for download. Your citation decides about the acceptance, distribution, and impact of this piece of knowledge. Please enjoy reading and may this book help promote the progress in ceramic development for better life on earth.